Mano de tierra (2020)
Mano de Tierra is a design project that aims to destigmatize the normalized imaginary of savages that Colombians have of Afro-Colombian population of the Pacific Coast. A social imaginary that has been built since Hispanic times and has not managed to dissipate within today's society thanks to the perpetuation of this stereotype throughout Colombian history. Two fundamental pillars were established. The first, spirituality, understood as an intangible dimension that gives reason to being, and the second, corp-orality, defined as an idiosyncratic socialization process between the individual and the other?. Both factors determine part of the African heritage and represent a differentiating pride within the culture itself. Within the corp-orality, a category of analysis emerges (in relation to the ?others?) that is taken as the axis of development of the project. It is understood that in order to mitigate this stereotype, it is necessary to analyze how the collective imaginary has permeated from colonial times to the present and how corp-orality and spirituality have been transformed within the Afro culture. To formulate this analysis, two approaches are proposed that allowed us to understand how the reproductions of the stereotype have been built within the Colombian social context. The first, a qualitative survey, and the second, the book 1000 Afro Caricatures in the history of Colombia by óscar Perdomo Gamboa. After this analysis, three Afro cultural manifestations are presented where nature emerges as an important pillar for this paradigm shift formulation. It is hoped to blur the savage stereotype that has been unconsciously constructed within the social imaginary of Afro-Colombians and thus sensitize the other so that it generates new dialogs of validation and respect for the Afro culture.